The physiology of emotional & irrational investing : causes and solutions - Zehndorfer, Elesa (Routledge, 2018)
"The financial markets are a rollercoaster and this book follows the same theme the seduction of money, our ruinous, heady and high stakes pursuit of it, the incredible fortunes and calamitous losses that have been made in its name, the new and significant threat of retail (armchair) investors wanting their piece of the pie, and the perpetual and foolish mismatch that has always existed and will always exist between our evolutionary programming and the design of the financial markets. The dominant theme that runs throughout the book ('Working out Wall Street') is actually a play on words, and relates both to the need to work out why Wall Street traders act so irrationally (e.g. using behavioural finance and evolutionary design to explain herding and panic selling), and the need to use physiological and sport science-related approaches to explain why working out (i.e. adopting exercise and diet-related practices usually applied to athletes) can significantly counter these behaviours. The phrase 'animal spirits' utilised in the concluding chapter title ('Taming Animal Spirits') refers to the seminal work of John Maynard Keynes in his 1936 classic work The General Theory of Employment, Interest and Money and the idea that human emotions-animal spirits- remain a significant driver in (irrational and emotional) investing. The rationale for this book is clear; behavioural finance and neurofinance have opened the floodgates in terms of recognising the role of emotional investing in cyclical boom-and-bust scenarios but what is still missing is an answer to the question So what do we do about it? This book seeks, in as compelling and entertaining a fashion as possible, to provide that answer."--Publisher description.